Psychometric Properties of Hindi Version of Physical Activity Recall Assessment for People with Spinal Cord Injury - Heeral Joshi1 , Shambhovi Mitra2 , Rajeev Aggrawal3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: The most widely used type of physical activity measure is the self-report survey. Of the available self-report physical activity measures, the vast majorities were developed for use in the general population and typically focus on measuring participation in recreational and sport activities. As a result, the existing self-report measures are insufficiently sensitive to measure very low intensity activities that might account for the bulk of daily energy expenditure among people with SCI. The content of these measures also fails to capture activities that are part of SCI lifestyle. ‘Physical Activity Recall Assessment for People with Spinal Cord Injury’ [PARA-SCI] was published in August 2005. PARA-SCI is a measure of physical activity for individuals with SCI who use a wheelchair as their primary mode of mobility. It has been translated in various languages, thus the aim of the study is to study the psychometric properties of Hindi version of physical activity recall assessment-SCI. Methods: PARA SCI was translated in phase 1 of the study and the reliability and validity of the instrument was done Results: There was significant correlation observed in test –retest reliability and Vo2 max calculated by 12 minute wheelchair test correlated with the subcomponent of PARA SCI Conclusion: The Hindi version of PARA-SCI is a reliable and valid instrument